Российская провинция: практики преодоления дефицита власти - Скиперских, Александр Владимирович (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2019)
In this article, the author, addressing different aspects of Russian culture, tries to understand how the institutions of power can function in the Russian provinces, and how they can be perceived by society. Power is distributed unevenly, which results in its deficit. From the author’s point of view, modern practices may have an important cultural basis, involving a special relation to the province, which has traditionally been reflected in political discourse. The author believes that in the Russian provinces, there is an objective power deficit in institutions, which speaks, on the one hand, of a certain disregard for the province, and, on the other hand, testifies to the strength of the resistance to local initiatives and the legal nihilism that has become part of the philosophy of the Russian provincial. This in turn affects a fairly critical attitude towards the political power. A person is no longer capable of trusting the authorities and seeking support from them. The policy of the federal government in modern Russia gives rise to serious gaps between the center and the provinces, which can lead to a specific perception of power itself, and also lead to the formation of anarchic attitudes.